STRATEGI SOSIALISASI KESETARAAN GENDER: UPAYA NYATA DALAM MENINGKATKAN PERAN PEREMPUAN DALAM KEPEMIMPINAN ORGANISASI - Khotibul Umam; Dyah Purbaningrum; Iklim Matunasia Aci; Hendri Hermawan Adinugraha (LPPM Universitas Bina Bangsa, 2023)
This study aims to improve gender equality and leadership among female students at SMK Muhammadiyah Kajen. This research used an observational approach before implementing gender sensitivity through Socialization. Activities consisted of lectures on gender equality, question and answer sessions, and prize distribution for active participants. The study highlights the importance of gender equality in education and organizations, and the positive impact it has on community development. It also emphasized the need for collective efforts from all departments and awareness of gender issues to create an inclusive and equitable work environment. Gender equality is not just a moral issue but also a strategic approach to achieve maximum performance and long-term sustainability in organizations